2017
DOI: 10.1177/0959683617693901
|View full text |Cite
|
Sign up to set email alerts
|

Climate controls on tree growth in the Western Mediterranean

Abstract: The first large-scale network of tree-ring chronologies from the western Mediterranean (WM; 32°N-43°N, 10°W-17°E) is described and analyzed to identify the seasonal climatic signal in indices of annual ring width. Correlation and rotated empirical orthogonal function analyses are applied to 85 treering series and corresponding gridded climate data to assess the climate signal embedded in the network. Chronologies range in length from 80 to 1129 years. Monthly correlations and partial correlations show overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 73 publications
5
20
1
1
Order By: Relevance
“…Although precipitation is expected to increase globally, the Mediterranean Basin will likely experience drying due to the rise in temperature and changes in atmospheric circulation patterns (Collins et al, ). Specifically, precipitation over the Mediterranean Basin is known to be linked to changes in atmospheric circulation patterns such as the North Atlantic Oscillation (NAO; Fortuny, ; Kelley, Ting, Seager, & Kushnir, ; Kelley, Ting, Seager, & Kushnir,; Vicente‐Serrano et al, ), which has been demonstrated to influence forest growth in the Mediterranean region (Dorado‐Liñán, Zorita, et al, ; Piovesan & Schirone, ; Touchan et al, ). According to the information provided by instrumental records, the Mediterranean region has already been showing a significant increase in dryness over the last six decades (Hartmann et al, ) concurrent with an increase in the frequency of high NAO phases (Bladé, Liebmann, Fortuny, & Oldenborgh, ; Folland et al, ), and drying will likely continue during the next century (Gao & Giorgi, ; Ozturk, Ceber, Türkeş, & Kurnaz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although precipitation is expected to increase globally, the Mediterranean Basin will likely experience drying due to the rise in temperature and changes in atmospheric circulation patterns (Collins et al, ). Specifically, precipitation over the Mediterranean Basin is known to be linked to changes in atmospheric circulation patterns such as the North Atlantic Oscillation (NAO; Fortuny, ; Kelley, Ting, Seager, & Kushnir, ; Kelley, Ting, Seager, & Kushnir,; Vicente‐Serrano et al, ), which has been demonstrated to influence forest growth in the Mediterranean region (Dorado‐Liñán, Zorita, et al, ; Piovesan & Schirone, ; Touchan et al, ). According to the information provided by instrumental records, the Mediterranean region has already been showing a significant increase in dryness over the last six decades (Hartmann et al, ) concurrent with an increase in the frequency of high NAO phases (Bladé, Liebmann, Fortuny, & Oldenborgh, ; Folland et al, ), and drying will likely continue during the next century (Gao & Giorgi, ; Ozturk, Ceber, Türkeş, & Kurnaz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cheddadi et al, 1998;Campbell et al, 2017;Zielhofer et al, 2017aZielhofer et al, , 2019. However, other factors such as winter temperature (Touchan et al, 2017), or ecological and edaphic conditions could have also influenced Cedrus expansion. Indeed, C. atlantica is a drought-tolerant species (but is sensitive to extreme drought; Aussenac, 1984;Rhanem, 2011) and is found growing in semi-arid mountain areas across North Africa (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The Atlas cedar has an important place in the Mediterranean landscape in Algeria and Morocco [8]. Unfortunately, the status of Atlas cedar stands in Algeria indicates a strong degradation linked primarily to anthropogenic action and the unfavorable climatic conditions marked by persistent drought since the 1980s [9] [10]. This situation has led to a loss of vitality and the emergence of tree decline [11] [12].…”
Section: Introductionmentioning
confidence: 99%